On the Existence of Optimal Stationary Equilibria with a Fixed Supply of Fiat Money: I. The Case of a Single Consumer - Benveniste, Lawrence M.; Cass, David (Journal of Political Economy, 1986)
This paper generalizes Samuelson's well-known analysis concerning the use of fiat or outside money to support Pareto-optimal allocations in an overlapping- generations framework. While maintaining an elementary demographic structure butexpanding the list of available commodities in each period, we establish the following result: If there is a fixed supply of fiat money, and individuals are also permitted to issue bonds or inside money, then there always exists at least one stationary equilibrium yielding a Pareto-optimal allocation.